Deformation needs in a nursing home: techniques for mobilizing assisted people (Cuestiones de Fisioterapia, 2006)
At the present time the figure of the geriatrical residence ocuppies a very important place in the society. In interdisciplinary's attention that is carried out in these, the paper of the physiotherapy that has already been made essential. After four years of labor experiencie in a geriatrical residence like physiotherapist and three years of occupational training imparting courses of infirmary's auxiliary in geriatrics, I would like to emhasize the so important necessity that as far as formation on techniques of attended people's mobilization has infirmary's auxiliary in a residence of old men. Secondly, I would like to propose a guide, summarizing what techniques are most correct to mobilize these patients' preventing lesions in the work, helping to improve the quality of the old men life and their independency and collaborating with the work of the physiotherapist.